Letter to the Editor. (September 2008) - Phelan, Ryan; Borry, Pascal; Howard, Heidi C
In response to: Howard HC, Borry P: Direct-to-consumer genetic testing: more questions than benefits? Personalized Med. 5(4), 317––320 (2008).